The Influence of Corporate Social Responsibility, Good Corporate Governance, and Climate Disclosure on Company Performance in The Palm Oil Industry - Yunita, Yudha Puspa (Manunggal Halim Jaya, 2025)
This study examines the influence of corporate social responsibility, good corporate governance, and climate disclosure on company performance in the palm oil industry. Unlike previous research, this study incorporates IFRS S2 as a factor in climate disclosure to assess its impact on company performance. The study employs a quantitative method using secondary data from the financial reports of palm oil companies listed on the Indonesia Stock Exchange for 2019–2023. The sampling technique used is purposive sampling. The results indicate that corporate social responsibility, good corporate governance, and climate disclosure positively and significantly impact company performance. The implications of this study highlight the importance of enhancing transparency in climate disclosure by IFRS S2 standards and improving CSR practices to strengthen the competitiveness of the palm oil industry.